Adaptation of Water, Sanitation, and Hygiene Interventions: A Model and Scoping Review of Key Concepts and Tools - Anderson, Darcy M.; Birken, Sarah A.; Bartram, Jamie K.; Freeman, Matthew C. (Frontiers in Health Services, 2022)
Background: Safe water, sanitation, and hygiene (WaSH) is important for health, livelihoods, and economic development, but WaSH programs have often underdelivered on expected health benefits. Underperformance has been attributed partly to poor ability to retain effectiveness following adaptation to facilitate WaSH programs’ implementation in diverse contexts. Adaptation of WaSH interventions is common but often not done systematically, leading to poor outcomes. Models and frameworks from the adaptation literature have potential to improve WaSH adaptation to facilitate implementation and retain effectiveness. However, these models and frameworks were designed in a healthcare context, and WaSH interventions are typically implemented outside traditional health system channels. The purpose of our work was to develop an adaptation model tailored specifically to the context of WaSH interventions. Methods: We conducted a scoping review to identify key adaptation steps and identify tools to support systematic adaptation. To identify relevant literature, we conducted a citation search based on three recently published reviews on adaptation. We also conducted a systematic database search for examples of WaSH adaptation. We developed a preliminary model based on steps commonly identified across models in adaptation literature, and then tailored the model to the WaSH context using studies yielded by our systematic search. We compiled a list of tools to support systematic data collection and decision-making throughout adaptation from all included studies. Results and conclusions: Our model presents adaptation steps in five phases: intervention selection, assessment, preparation, implementation, and sustainment. Phases for assessment through sustainment are depicted as iterative, reflecting that once an intervention is selected, adaptation is a continual process. Our model reflects the specific context of WaSH by including steps to engage non-health and lay implementers and to build consensus among diverse stakeholders with potentially competing priorities. We build on prior adaptation literature by compiling tools to support systematic data collection and decision-making, and we describe how they can be used throughout adaptation steps. Our model is intended to improve program outcomes by systematizing adaptation processes and provides an example of how systematic adaptation can occur for interventions with health goals but that are implemented outside conventional health system channels.